A Graphdiyne Oxide‐Based Iron Sponge with Photothermally Enhanced Tumor‐Specific Fenton Chemistry. Issue 31 (28th June 2020) - Min, Huan; Qi, Yingqiu; Zhang, Yinlong; Han, Xuexiang; Cheng, Keman; Liu, Ying; Liu, Huibiao; Hu, Jianshe; Nie, Guangjun; Li, Yiye
Abstract: Fenton reaction‐mediated oncotherapy is an emerging strategy which uses iron ions to catalytically convert endogenous hydrogen peroxide into hydroxyl radicals, the most reactive oxygen species found in biology, for efficient cancer therapy. However, Fenton reaction efficiency in tumor tissue is typically limited due to restrictive conditions. One strategy to overcome this obstacle is to increase the temperature specifically at the tumor site. Herein, a tumor‐targeting iron sponge (TTIS) nanocomposite based on graphdiyne oxide, which has a high affinity for iron is described. TTIS can accumulate in tumor tissue by decoration with a tumor‐targeting polymer to enable tumor photoacoustic and magnetic resonance imaging. With its excellent photothermal conversion efficiency (37.5%), TTIS is an efficient photothermal therapy (PTT) agent. Moreover, the heat produced in the process of PTT can accelerate the release of iron ions from TTIS and simultaneously enhance the efficiency of the Fenton reaction, thus achieving a combined PTT and Fenton reaction‐mediated cancer therapy. This work introduces a graphdiyne oxide‐based iron sponge that exerts an enhanced antitumor effect through PTT and Fenton chemistry. Abstract : A tumor‐targeting iron sponge (TTIS) based on graphdiyne oxide is fabricated with controlled iron release. The TTIS can accumulate in tumor tissue to achieve photoacoustic‐ and magnetic resonance tumor imaging, and simultaneously escort an efficient tumor therapy via photothermally enhanced Fenton chemistry.